Occupational exposure to magnetic fields and the risk of somatic and psychological symptoms among sewing machine operators. (23rd July 2020) - Jalilian, Hamed; Gorjizadeh, Omid; Zamanian, Zahra; Hajizadeh, Zeynab; Röösli, Martin; Monazzam, Mohammad Reza; Najimi, Mohammadreza
This study aimed to assess the occupational exposure to extremely low frequency magnetic fields (ELF-MF) and static magnetic fields (SMF) and their relationship to health problems among tailors. Totally, 71 male tailors (exposure group) and 60 male clothing retailers (control group) participated in the study and completed three questionnaires. ELF-MF and SMF were measured in four levels of body organs in three states of sewing machine by two instruments. A significant risk for somatic symptoms (odds ratio [OR]: 1.58; 95% confidence intervals [CI]: 1.02, 2.46), sleep disorders (OR: 1.68; 95%CI: 1.04, 2.78), dizziness (OR: 1.58; 95%CI: 1.00, 2.85), and fatigue (OR: 1.67; 95%CI: 1.00, 2.85) were observed. The tailors occupationally were exposed to 1.78 μT ELF-MF and less than 0.1 mT SMF on average. The tailors were more likely to have somatic and psychological disorders. Long term ELFMF exposure might be a potential cause for these problems.